Metode Hypnoteaching melalui Neuro Linguistic Programming (NLP) dalam Keterampilan Berbicara Bahasa Arab - Alvina, Vikria Tahta; Haryati, Ratih; Hilmi, Mustafiqul; Hilmi, Danial (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This qualitative descriptive research with a literature review design adopts the hypnoteaching method through the Neuro-Linguistic Programming (NLP) approach as an innovative effort to enhance students' motivation in speaking the Arabic language. The study's research question is if the hypnoteaching approach based on Neuro-Linguistic Programming (NLP) can boost students' motivation to speak Arabic. The study's findings suggest that the hypnoteaching method and Neuro-Linguistic Programming (NLP) are useful in educational growth, especially the Arabic language. The steps of hypnoteaching involve motivation, pacing, leading, positive words, praise, modeling, and teacher expertise. The application of NLP involves understanding students' characteristics, using outcomes, rapport, sensory acuity, and flexibility. Furthermore, the use of hypnoteaching through NLP in learning Arabic speaking can be an effort to enhance students' learning motivation, create more effective learning, overcome psychological barriers, and encourage students' motivation to actively develop Arabic speaking skills. Thus, this forms a strong foundation for the significant development of students' speaking skills.